2016
DOI: 10.3168/jds.2015-10724
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a mycoplasma molecular diagnostic test and distribution of mycoplasma species in bovine milk among New York State dairy farms

Abstract: Mycoplasma mastitis is a contagious and costly disease of dairy cattle that significantly affects animal health and milk productivity. Mycoplasma bovis is the most prevalent and invasive agent of mycoplasma mastitis in dairy cattle, and early detection is critical. Other mycoplasma have been isolated from milk; however, the role and prevalence of these species as mastitis pathogens are poorly understood. Routine screening of milk for mycoplasma by bacteriological culture is an important component of a farm con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…Primers and annealing conditions for MH, PM, and HS were as described by Klima et al [2]. For MB, the three targets included uvrC, 16S rDNA, and Mycoplasma 16S to 23S rDNA intergenic transcribed spacer region with primers and annealing conditions as described by Gioia et al [19]. Only PCR-confirmed MH, PM, HS, or MB isolates were included in subsequent analyses.…”
Section: Pcr Confirmation Of Species and Detection Of Amr Genesmentioning
confidence: 99%
“…Primers and annealing conditions for MH, PM, and HS were as described by Klima et al [2]. For MB, the three targets included uvrC, 16S rDNA, and Mycoplasma 16S to 23S rDNA intergenic transcribed spacer region with primers and annealing conditions as described by Gioia et al [19]. Only PCR-confirmed MH, PM, HS, or MB isolates were included in subsequent analyses.…”
Section: Pcr Confirmation Of Species and Detection Of Amr Genesmentioning
confidence: 99%
“…In general, molecular methods can be divided into those allowing specific detection of M. bovis (using either conventional or real‐time PCRs; Cai, Bell‐Rogers, Parker, & Prescott, ; Ghadersohi, ; Hotzel, Sachse, & Pfützner, ; Rossetti, Frey, & Pilo, ; Sachse et al., ; Subramaniam et al., ) and those allowing simultaneous detection of M. bovis with other mycoplasma species or Mollicutes . The latter includes multiplex PCRs (Boonyayatra et al., ; Cornelissen et al., ; Gioia, Werner, Nydam, & Moroni, ; Justice‐Allen, Trujillo, Goodell, & Wilson, ; Parker, House, Hazelton, Bosward, & Sheehy, ; Righter, Rurangirwa, Call, & McElwain, ), PCR with denaturing gradient gel electrophoresis (DGGE); (McAuliffe, Ellis, Lawes, Ayling, & Nicholas, ) and a DNA microarray based on oligonucleotide probes derived from the 23S rRNA gene and species‐specific probes from the tuf gene target (Bottinelli et al., ; Schnee et al., ). It is important to note that although multiplex detection may help in the diagnosis of mixed mollicute infections, it may introduce additional complexity into the determination of disease aetiology; multiple mycoplasma species may be found, for example, in the upper respiratory or genital tracts that are apparent commensals with questionable significance in disease (Brown et al., ).…”
Section: The Causative Organismmentioning
confidence: 99%
“…We also followed the steps of Gioia et al (2016) Compared to other bacterial pathogens, the current knowledge of the molecular basis of pathogenicity of mycoplasmas is limited, and disruption at the molecular and cellular level remain to be elucidated. Several studies in the past years have shown that pathogenic mycoplasmas are equipped with sophisticated genetic systems, which allow these agents to spontaneously change their surface antigenic make-up (Jeqchlingeret al, 2004;Chopra-Dewasthaly et al, 2017).…”
Section: Discussionmentioning
confidence: 99%